Study on the Dynamic Deformation Characteristics of Artificial Structural Loess - Yu Xi; Mingming Sun; Xueqing Hua; Yao Zhang; Ye Yuan (Buildings)
Due to the difficulties in sampling, high sensitivity to humidity, and inconvenience in storage, undisturbed loess is prone to changes in its original structure. Therefore, trace amounts of cement and salt are added to remolded soil to simulate the structure of undisturbed loess. The GDS dynamic three-axial test apparatus was used to investigate the influence of dry density, cement content, and confining pressure (CP) on the dynamic distortion characteristics of artificially structured soil. Based on dynamic triaxial tests, the Hardin–Drnevich (H-D) model was established through fitting analysis. The research findings indicate that increased dry density, cement content, and CP can enhance the soil’s resistance to distortion. Under dynamic loading, the higher the CP, the smaller the damping ratio of the soil. With a dry density of 1.20 g/cm3 and 2% cement, the dynamic modulus of the artificially structured loess is similar to that of undisturbed loess. With a dry density of 1.60 g/cm3 and 2% cement, the CP is 200 kPa, the soil’s dynamic modulus of elasticity (DM-E) peak value is 113.14 MPa, and the damping ratio is 0.258. The good agreement between trial data and the predicted results demonstrates that the H-D hyperbolic model is appropriate for representing the DM-E of artificially structured loess. A three-dimensional model of the dynamic deformation characteristics and microstructure of artificial structural loess under dynamic loads was established. The findings can guide the study of the mechanical properties of loess under dynamic loading.